Comparison of Safety and Efficacy of Ebastine with Levocetirizine in Treating Chronic Idiopathic Urticaria - Dr. A. Anitha; Dr. J Srujani; Dr. Sowmya B; Dr. Srinivas P (International Journal of Pharma and Bio Sciences, 2024)
Chronic idiopathic urticaria (CIU) is a routine skin disease affecting the general population because of chronic infections, allergy to certain foods, anxiety, and autoantibodies against IgE receptors. Second-generation non-sedating H1 antihistamines are the most used drugs in the management of CIU. The current study aims to assess the efficacy and safety of Ebastine and Levocetirizine in CIU and to assess the improvement in UAS (urticarial activity score) with the treatment. 150 patients with CIU attending the department of dermatology, venereology and leprosy (DVL) in government general hospital, Ananthapuram, were randomly allocated into two groups with 75 patients in each group. Group A patients received Ebastine 20 mg once daily for 12 weeks’ group B patients received a levocetirizine 5mg once daily for 12 weeks. Based on the urticarial activity scores (UAS7), the Antihistaminic response is noted. The mean age of the patients was 34.2 years. At baseline, the mean UAS7 score was 5.37; in the 12th week, the score was 2.00 in the Ebastine group. The mean UAS7 score was 5.15 in the Levocetirizine group and 2.67 at the end of the 12th week. There is a significant difference in the score. We found that levocetirizine 5mg has more side effects suchas mouth dryness and sedation than Ebastine 20mg. The study concluded that Ebastine 20mg is safer, more productive, and more tolerable, with fewer side effects than Levocetirizine 5mg.